An Integrated Forecasting Model for Electricity Demand in a Power System Considering Time Difference between Criteria. Issue 4 (May 2020) - Huo, Huijuan; Liu, Yijiang; Ma, Tiannan; Wang, Hongjin; Lu, Yanchao
Abstract: As China's economy enters a stage of high-quality development, the trend of the power demand has changed and can affect the investment and construction of power industry. A series of key criteria impacting on power demand were sorter out to build a power demand index system currently. The time difference correlation analysis was applied to classify these criteria as precursor, consistency and lag index. The power demand index based on the three categories of criteria were fitted based on the multivariate statistical analysis. Then the comprehensive power demand index was assembled to forecast the electric power demand from 2020 to 2022 in China based on the current policy and economic situation.